Kesehatan Ekosistem Padang Lamun di Perairan Tukak dengan Metode Seagrass Ecological Quality Index (SEQI) - Handayani, Ferly; Hudatwi, Mu’alimah; Utami, Eva (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2024)
Seagrass ecosystems have a very important role in coastal areas, namely as carbon stocks and storage. Seagrass beds in Tukak Village are seriously threatened by mining activities and the development of shrimp ponds in coastal areas. The important role of seagrass meadows and the high threat from anthropogenic activities, however, there is very little data and information on the health condition of seagrass meadows in Tukak Village. While seagrass health data is very important as an effort to protect and restore seagrass ecosystems. The research objectives included: 1) Analyzing the health and condition of seagrass beds in Tukak Beach, South Bangka Regency, 2) Analyzing the percentage of seagrass cover and species richness in Tukak Beach, South Bangka Regency. The research was conducted in September 2023 at Tukak Beach. The research stages consisted of 1) Station point determination, 2) Seagrass, macroalgae and epiphyte data collection, 3) Measurement of environmental parameters, 4) Data analysis includes analysis of seagrass health with the Seagrass Ecological Quality Index (SEQI) method and calculation of Epiphyte Cover on seagrass leaves. The richness of seagrass species found in Tukak Village during the research amounted to 6 species, namely Enhalus acoroides (EA), Thalassia hemprichii (TH), Oceana serrulata (OS), Halodule uninervis (HU), Halophila ovalis (HO) and Syringodium isoetifolium (SI). The most dominating seagrass is Thalassia hemprichii (TH). Seagrass cover in Tukak Village is categorized as moderate to good with a range of seagrass cover of 20.64% to 24.59%. Seagrass cover that is categorized as rare is found at Station 3 with a cover of 20.64%. While the most seagrass cover category is found at Station 1 with a cover of 24.59%. The results of the seagrass health analysis of seagrass conditions in Tukak Waters are categorized as Moderate to Good. Moderate conditions are found at Station 2 with a value of 0.68, while the good category is found at Stations 1 and 3 with values of 0.75 and 0.71.